Pengaruh Penggunaan Serbuk Arang Batok Kelapa Terhadap Kuat Tekan Beton - Eransyah, Muhammad Fitra; Paryati, Ninik; Sylviana, Rika (CV. Information Technology Training Center - Indonesia (ITTC), 2022)
Processing of coconut shells into charcoal powder as a concrete mixture. The use of coconut shell charcoal powder on the compressive strength of concrete aims to be a substitute for cement for normal concrete compressive strength and to determine the optimum concrete compressive strength after substitution of cement using coconut shell charcoal powder. In this study the use of coconut shell charcoal powder as a cement substitution with variations of 0%, 2.5%, 5% and 7.5%. Concrete testing was carried out at the age of 28 days after treatment by being immersed in water. The results of the analysis showed that the average compressive strength value of the addition of coconut shell charcoal powder at variations of 5% and 7.5% decreased by 11% and 12.57% because with the increasing number of calcium hydroxide formed, the cement adhesion will decrease so that the structure inside will be weak and cause the compressive strength to be low, while the variation of adding coconut shell charcoal powder 2.5% has an increase of 2.07% against normal concrete compressive strength. From the results of the characteristic concrete compressive strength obtained with substitution variations of 2.5%, 5%, and 7.5% respectively of 278.74 kg/cm2, 243.43 kg/cm2 and 238.96 kg/cm2, the concrete These include class II K 275 concrete (middle class concrete) structural concrete.